2022
DOI: 10.3390/polym14214744
|View full text |Cite
|
Sign up to set email alerts
|

Flexible Investment Casting Wax Patterns for 3D-Printing: Their Rheological and Mechanical Characterizations

Abstract: The mechanical and rheological characterizations of flexible investment casting patterns capable of 3D printing are reported. The wax pattern was composed of microcrystalline hydrocarbon wax (DMW7478), Piccotex 75 (a copolymer of α–methyl–styrene and vinyl toluene with a 75/25 molar ratio, respectively) and Escorene (a copolymer of ethylene and vinyl acetate with a 72/28 mass ratio, respectively). It was found that in order to obtain a wax pattern with appreciable mechanical properties, the content of the micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…The mechanical parameters of additive-manufactured polymers can be enhanced with heat treatment after the printing process [ 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 ]. The material properties of 3D-printed samples can be characterized via material testing [ 26 , 27 ]. Several researchers have conducted tensile tests to determine FDM-printed and heat-treated specimens’ mechanical properties, measuring the increase in UTS (32%) by annealing the specimens at 90 °C for 1 h [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…The mechanical parameters of additive-manufactured polymers can be enhanced with heat treatment after the printing process [ 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 ]. The material properties of 3D-printed samples can be characterized via material testing [ 26 , 27 ]. Several researchers have conducted tensile tests to determine FDM-printed and heat-treated specimens’ mechanical properties, measuring the increase in UTS (32%) by annealing the specimens at 90 °C for 1 h [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Wax is one of the thermoplastic materials that has been utilized for the longest in recorded human history. Due to their varied and variable qualities, which allow them to generate final products that meet a variety of needs, waxes are primarily utilized in foundries such as the production of wax patterns in traditional investment casting process [13]. The next step includes the investment casting of the wax patterns of the selected product.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, the affordability and availability of FFF machines make the technology the most popular in the AM industry. In addition, recent studies demonstrated that it is possible to manufacture low-cost wax patterns having properties very similar to traditional IC waxes [ 8 , 9 ]. For example, non-tough wax parts having low viscosity in the molten state have been manufactured by the authors of the current study [ 8 ].…”
Section: Introductionmentioning
confidence: 99%